An innovative three-layer strategy in response to a quartan malaria outbreak among forest goers in Hainan Island, China: a retrospective study - Yuchun Li; Yingjuan Huang; Renqiang Chen; Weizhen Huang; Huanzhi Xu; Rongshen Ye; Shaoling Huang; Ji Zhen; Xiaodan Wen; Guoyi Wang; Yong Liu; Haishan Li; et al. (BMC, 2022)
Abstract Background An outbreak of Plasmodium malariae infection among forest goers in Sanya City of Hainan Island, China was reported in 2015. In response to this outbreak, an innovative three-layer strategy (TLS) targeted forest goers was adapted based on the 1-3-7 approach. Main text Key elements of TLS are: (i) The village with five malaria cases and adjacent villages were set as the first layer. All residents including forest goers were taken as the high-risk population (HRP). Active case detection (ACD) by blood smear microscopy and PCR was selected as the primary measure, and passive case detection (PCD) as complementary measure. One case was identified under TLS implementation. (ii) The township with cases (Gaofeng Town) and the nearby towns were chosen as the second layer. Only forest goers were screened by ACD, while PCD as a routine screening method. 7831 blood smears collected by ACD and PCD and tested with negative results. (iii) The city with cases (Sanya City) and others 12 counties/county-level cities were selected as the third layer. Malaria cases were monitored passively. A total of 77,555 blood slides were screened by PCD with zero positive sample. For each layer, the malaria vector mosquitoes were monitored using light traps, cattle-baited/human-bait traps. Anopheles minimus (dominant species), An. sinensis and An. dirus were captured. Vector control measures mainly include insecticide residual spraying and long-lasting insecticide nets. The capacity of clinicians, public health practitioners and laboratory technicians has been improved through training. During 2016‒2018, TLS and chemoprophylaxis were implemented in the same areas. In the first layer, all residents were monitored by ACD, and malaria chemoprophylaxis were distributed, 89.5% of forest goers were using chemoprophylaxis against malaria. The blood smears (3126 by ACD plus 1516 by PCD) were with zero positive results. Chemoprophylaxis and ACD were offered to forest goers once a year, and PCD in residents as a complementary measure in the second and third layer, 77.8% and 95.1% of forest goers received chemoprophylaxis. In each layer, vector surveillance and control of malaria and trainings for medical staff were still in place. Conclusions TLS was effective in blocking the outbreak by P. malariae among forest goers in Hainan in malaria elimination stage. However, whether it could prevent the malaria resurgence in the post-elimination phase needs to be further assessed. Graphical Abstract